INTELLECTUAL CAPITAL IN ISLAMIC HIGHER EDUCATION: PESANTREN-BASED INSTITUTIONS - Mustikawan, Alfin; Maimun, Agus; Listyo Prabowo, Sugeng (Evaluasi: Jurnal Manajemen Pendidikan Islam, 2024)
This research examines the intellectual capital (IC) at STAI Attanwir Bojonegoro, an Islamic higher education institution based on pesantren principles. The objective is to analyze the institution's human capital, structural capital, and relational capital, along with the challenges faced in managing IC in the digital era. A qualitative descriptive approach was employed, gathering data through in-depth interviews and documentary studies. The findings reveal that STAI Attanwir possesses strong human capital in terms of academic competence and Islamic knowledge among teaching staff and educational personnel. Structural capital is evident in the physical infrastructure and integrated information systems such as SIM STAI Attanwir, while relational capital is demonstrated through partnerships with community organizations, government entities, and alumni. Key challenges identified include adapting to technological advancements and managing social and political issues like radicalism. The research concludes by emphasizing the critical role of IC management as a strategy to enhance educational quality and institutional competitiveness in an increasingly competitive future.